An educational intervention to reduce pain and improve pain management for Malawian people living with HIV/AIDS and their family carers: study protocol for a randomised controlled trial - Nkhoma, Kennedy; Seymour, Jane; Arthur, Antony (BioMed Central, 2013)
Many HIV/AIDS patients experience pain often due to advanced HIV/AIDS infection and side effects of treatment. In sub-Saharan Africa, pain management for people with HIV/AIDS is suboptimal. With survival extended as a direct consequence of improved access to antiretroviral therapy, the prevalence of HIV/AIDS related pain is increasing. As most care is provided at home, the management of pain requires patient and family involvement. Pain education is an important aspect in the management of pain in HIV/AIDS patients. Studies of the effectiveness of pain education interventions for people with HIV/AIDS have been conducted almost exclusively in western countries.